Hubungan pengetahuan ibu tentang gizi Dengan status gizi anaka usia 1-3 tahun - Rika - Susanti; Ganis - Indriati; Wasisto - Utomo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
This study’s aims to determined the correlation of mother’s knowledge about children nutrition and nutritional status of 1-3 years old children. This study used a descriptive correlative design with cross sectional approach undertaken mother’s of children aged 1-3 years in the area of Community Health Center of Rejosari, Tenayan Raya Sail district Pekanbaru. The total samples were 98 respondent, taken using a cluster sampling technique by consideret the inclusion criteria. Measuring instrument used was a questionnaire that has been tested for validity and reliability along with scales. The analysis used univariate and bivariate by using pearson chi-square. The results showed a correlation between mother’s knowledge about children nutrition and nutritional status of 1-3 years old children (p value 0.004 < α 0.05). This study recommends to every health care proffesional to increases the mother’s  knowledge about nutrition so they could improved nutritional status of their children. Keywords: Knowledge, nutritional status.